BIOGRAPHY AND CONTRIBUTION TO SCIENCE OF LONJID NAMGAR (1922-2004), THE FAMOUS SCIENTIST OF THE 20th CENTURY AND THE MONGOLIAN STATE AWARD RECIPIENT (Mongolian Journal of Geography and Geoecology, 2022)
ХОРЬДУГААР ЗУУНЫ НЭРТ ЭРДЭМТЭН, МОНГОЛ УЛСЫН ТӨРИЙН ШАГНАЛТ НАМГАРЫН ЛОНЖИД АГСНЫ НАМТАР, ШИНЖЛЭХ УХААНД ОРУУЛСАН ХУВЬ НЭМЭР (1922-2004)